Welcome to the first issue of the journal for 2018 - Daniels, H (Taylor and Francis, 2018)
In the first article of the issue, Hannah Margraf and Martin Pinquart discuss differences between regular and special schools in the impact of maternal responsiveness and control on change in externalizing behaviour problems. They compared 124 adolescents from special schools for students with emotional and behavioural disturbances (EBD) and 133 regular schooled adolescents with regard to their perceived maternal behaviour. They noted an interaction effect of school type and parenting behaviour on externalising behaviour. They conclude with a discussion of maternal warmth/support for those attending special schools.